Enhancing Laboratory Safety in Nigerian Tertiary Institutions: An Investigation into the Effectiveness of Implemented Safety Measures - Olusegun, Bisola Esther; Onowugbeda, Franklin U; Noah, Charles Benedict; Nafiu, Halimat Dupe (Journal of Education For Sustainable Innovation, 2025)
Abstract This study explores the implementation, effectiveness, and challenges of laboratory safety practices in Nigerian tertiary institutions, with a focus on the College of Science Education at Lagos State University of Education. Adopting a descriptive survey design, data were collected from 400 participants consisting 300 students, 50 laboratory staff, and 50 lecturers selected through random sampling. A validated questionnaire (Cronbach’s alpha = 0.75) ensured internal consistency. Both descriptive and inferential statistics were employed for analysis. Findings indicate that safety measures such as clear communication of guidelines, mandatory use of personal protective equipment (PPE), and periodic safety training are in place and moderately effective in reducing laboratory accidents. However, gaps remain in emergency preparedness, frequency of drills, and the adequacy of safety infrastructure. Approximately 30–35% of respondents reported insufficient training and irregular safety drills. The study concludes that while safety protocols are acknowledged, inconsistent enforcement and limited resources hinder their full implementation. It recommends improved funding for safety infrastructure, regular training for laboratory personnel, and stricter enforcement of safety policies. Promoting a proactive safety culture through collaboration among educators, administrators, and policymakers is essential. These findings provide actionable insights for improving laboratory safety and fostering a safer, more effective science education environment.